PENERAPAN MODEL PEMBELAJARAN TIPE NUMBER HEADS TOGETHER (NHT) BERBASIS PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR IPA - Yuri Afta; Clarry Sada; Rosalyna Yoesi Etiovia (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: The purpose of this research is to know the result of science study result of fourth grade students atPublic Elementary School Number 02 Batu Buil prior and following the application cooperative learning model type NHT withscientific-based approach, and also to find out the science study resultprior and following the use of conventional method and to know the significant difference between the application method of conventional learning and NHT-based with scientific approaches to science study result. The research method used was Quasi Eksperimental Design using The Nonequivalent Control Group Design form. The population in this research were the fourth grade students of SDN 02 Batu Buil. Sample in this research were class IV A and class IV B. The result of the research indicated that there were difference of science study result of the studentsprior theapplication of cooperative learning model type Heads Together (NHT) with scientific-based approach whichachieved tcount = 1,976 and ttable = 2,032 then Tcountttable. Following the implementation of cooperative learning model type Head Head Together (NHT) with scientific-based approach obtained tcount = 2,988 and ttable = 2,032 which resulted in tcount ttable.Keywords: application of learning model type head head together (nht), scientific approach and studentsstudy resultAbstrak: Tujuan penelitian ini ialah untuk mengetahui hasil belajar IPA siswa kelas IV SDN 02 Batu Buil sebelum dan setelah menggunakan model pembelajaran kooperatif tipe NHT berbasis pendekatan saintifik, mengetahui hasil belajar IPA siswa sebelum dan setelah menggunakan metode konvensional dan mengetahui perbedaan yang signifikan antara penerapan metode konvensional dengan pembelajaran NHT berbasis pendekatan saintifik terhadap hasil belajar IPA. Metode penelitian adalah Quasi Eksperimental Design menggunakan bentuk The Nonequivalent Control Group Design. Populasi  dalam  penelitian  ini  adalah siswa kelas IV SDN 02 Batu Buil. Sampel dalam penelitian ini yaitu kelas IV A dan kelas IV B. Hasil penelitian menunjukan bahwa terdapat perbedaan hasil belajar IPA pada siswa sebelum diterapkannya model pembelajaran kooperatif tipe Number Heads Together (NHT) berbasis pendekatan saintifik yaitu dapat diperoleh thitung = 1,976 dan ttabel = 2,032 maka thitung ttabel.  Setelah diterapkannya model pembelajaran kooperatif tipe Number Heads Together (NHT) berbasis pendekatan saintifik yaitu memperoleh data thitung = 2,988 dan ttabel =2,032 maka thitung ttabel.Kata Kunci:   penerapan model pembelajaran tipe number heads together (nht),  pendekatan saintifik dan hasil belajar IPA siswa